Legal Policy of Old Wells Petroleum Mining Management Based on Social Justice in Realising Energy Sovereignty - Lego Karjoko; I Gusti Ayu Ketut Rachmi Handayani; Willy Naresta Hanum (Sriwijaya Law Review, 2022)
Indonesia has the potential for oil from old wells of 10,000 barrels per day, but this potential is not optimally regulated. Hence, its management cannot realise social justice. This research aims to provide a prescription for the distribution of benefits and public participation in managing petroleum in old wells because all provisions for old wells do not accommodate the public interest. This research uses normative legal research utilising a statutory, conceptual, and case approach to analyse the regulation policy related to old wells management. Data were collected by investigating primer and seconder legal material. The results show that the distribution of benefits related to profit-sharing for oil management services at old wells did not reflect justice. Thus, it is causing a lot of illegal mining activities. Moreover, public participation in determining policies is still at the pseudo participation (informing level). Therefore the actual participation has not been accommodated in related regulations of old wells management.